Penggunaan Alat Peraga Edukatif Media Tanah Liat Untuk Meningkatkan Kemampuan Mengenal Bentuk Geometri Pada Anak Usia Dini - Evi Rahayu; Syahri Ramadhan; Nelia Guswanti; Roby Seprya; Inmaryanto Inmaryanto (Mitra Ash-Shibyan: Jurnal Pendidikan dan Konseling, 2022)
Recognizing geometrical shapes for children is a children’s skill in recognizing, showing, stating, and collecting geometrical things. These processes start by introducing geometrical concepts by identifying the geometrical characteristics. The purpose of this study was to clarify the use of clay can improve the students’ skill of group B1 of TK Annisa, Tambang Sub-District, Kampar Regency on recognizing the geometrical shapes. This study belongs to Classroom Action Research (CAR). It was done in two cycles, in which each cycle consists of two meetings. This was completed in four steps, namely: planning, action, observation, and reflection. The results revealed the students’ skills in recognizing the geometric shapes were 35% in pre-cycle, 55.78% in cycle I, and 85% in cycle II. The overall improvement of the students’ skill in recognizing the geometrical shapes was on an average of 55.46%. Thus, the use of clay media educational teaching aids can improve the ability to recognize geometry in early childhood.